Persepsi Followers Terhadap Akun Instagram @Ammarzoni Pasca Tertangkap Narkoba Kedua Kali - Ruth Natasya Novianti Siagian; Sumardjijati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Instagram is one of the platforms of choice that is now widely used by individuals to carry out personal branding, develop business, educate, and so on. This is what gave birth to the phenomenon of mentioning the word 'influencer' on social media. This influencer figure often receives criticism or judgment from his followers, which can be called interpersonal perception. This research focuses on the perceptions of Ammar Zoni's followers towards the Instagram account @ammarzoni because of the pros and cons of his second drug case. This research uses interpersonal perception theory which aims to determine the diverse perceptions or views of each individual. The research method used is a qualitative descriptive method in order to uncover and explain the phenomenon being studied clearly and in detail. The data collection techniques used in this research are documentation and in-depth interviews. The results of this research show that there are differences in the impressions of Ammar Zoni's Instagram followers regarding the Instagram @ammarzoni case after the second drug, starting from the mysterious impression displayed on the @ammarzoni Instagram account, the feeling of pity for Ammar Zoni's family and himself as a result of his Instagram posts. , a little disappointed but still applauded because in Instagram posts @ammarzoni still shows his responsibility towards his two children, @ammarzoni's Instagram account is bad because of his drug actions, so he feels that Ammar Zoni's Instagram account is fake.